The Influence of Self-Efficacy, Organizational Climate and Work-Life Balance on Work Achievement through Motivation as an Intervening Variable - Lazuardi, Pascal; Badruzaman, Jajang; Rosliyati, Ati (SMART Insight, 2024)
This research aims to determine: (1) the influence of self-efficacy, organizational climate, and work-life balance on work motivation. (2) the influence of self-efficacy, organizational climate, and work-life balance on work performance. (3) the influence of work motivation on work performance. (4) the influence of self-efficacy, organizational climate, and work-life balance on work performance through work motivation. The sample size in this study was 251 respondents. This research is quantitative with a descriptive approach, using primary data and partial least squares structural equation model (PLS-SEM) analysis techniques. The results of this study conclude that: (1) there is a significant positive influence between organizational climate and work-life balance on employee work motivation, but self-efficacy has an insignificant effect. (2) There is no significant influence between self-efficacy, organizational climate, and work-life balance on work performance. (3) There is a significant positive influence between work motivation and work performance. (4) There is a significant positive influence between organizational climate and work-life balance on work performance through employee work motivation, but self-efficacy has an insignificant effect.